2016
DOI: 10.3409/fb64_2.89
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bromodeoxyuridine on Spontaneous Sister Chromatid Exchange Frequency in Rabbit (<I>Oryctolagus cuniculus</I>) and Coypu (<I>Myocastor coypu</I>) Chromosomes

Abstract: The effect of bromodeoxyuridine on spontaneous sister chromatid exchange frequency in rabbit (Oryctolagus cuniculus) and coypu (Myocastor coypu) chromosomes. Folia Biologica (Kraków) 64: 89-96. The sister chromatid exchange test is regarded as a highly sensitive cytogenetic assay. It measures chromosome sensitivity to particular damage factors and provides information on control and repair mechanism performance. It is instrumental in the early identification of the effects of noxious factors present in the hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Many scientists investigating sister chromatid exchanges claim that the sites where exchanges occur are not accidental and show species-specific variation. The location of SCEs in the chromosome is likely to be associated with different arrangements of heterochromatin in different species [32,50]. According to Latt [51] and Iannuzzi et al [52], SCEs are generated in the G-bands and in the areas between the bands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scientists investigating sister chromatid exchanges claim that the sites where exchanges occur are not accidental and show species-specific variation. The location of SCEs in the chromosome is likely to be associated with different arrangements of heterochromatin in different species [32,50]. According to Latt [51] and Iannuzzi et al [52], SCEs are generated in the G-bands and in the areas between the bands.…”
Section: Discussionmentioning
confidence: 99%
“…According to many researchers, exchanges take place less frequently in the terminal part of chromosomes [32,53]. On the other hand, Kuchta-Gładysz et al [50,54] have reported a very high level of damage in the distal part of the chromosome. Damage in this part of the chromosome is caused by oxidative stress, which results in single-strand DNA breakage in the telomeres.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of biomonitoring, it is necessary to know the level of spontaneous chromosomal and DNA damage in the population because it allows determining acceptable normal values and provides baseline data in the case of unexpected exposure to environmental or nutritional factors. In our previous study, we assessed spontaneous SCEs in coypu chromosomes (Kuchta‐Gładysz, Wójcik, Szeleszczuk, Niedbała, & Wojnar, 2016). To the authors’ knowledge, until now no studies have investigated genomic instability in coypu using FS, BLM, MN, and comet assays.…”
Section: Introductionmentioning
confidence: 99%